PROBLEMATIKA PERLINDUNGAN HUKUM TERHADAP KELOMPOK LESBIAN, GAY, BISEKSUAL, DAN TRANSGENDER (LGBT) DALAM PERSPEKTIF HAM INTERNASIONAL - Putu Dian Adnyani (Ganesha Law Review, 2022)
LGBT or Lesbian, Gay, Bisexual, and Transgender are behaviors that are currently a hot topic of conversation in the international community. This group which symbolizes itself with the rainbow flag has different views in term of sexual orientation, sexual characteristics, gender identity, and gender expression. It is still very difficult to accept their existence in society at large, so they often experience discrimination in the form of harassment, violence, threats, and so on, against the human rights of every human being. This article aims to understand more deeply about how the legal protection for LGBT groups, especially legal protections from the perspective of the Universal Declaration of Human Rights. The methoed used in the preparation of this scientific article is a qualitative descriptive method, therefore the approach used is a case study and literature study (library research) through various literatures in the form of journals, websites, e-books that are in accordance with the problems raised in this scientific article. The result of the research contained in this scientific article indicate that the LGBT group, who is also a human being, has the same rights as independent individuals so that they are entitled to legal protection from all violence, torture, and thearts are not in accordance with human values